Police Enforcement of Cycling Offences: A Case Study in Winnipeg, Manitoba - Orly Linovski; Aaron Snider (Findings)
Bias in policing is a concern in many Canadian cities, through there is little known about the impact on cyclists. This research analyzed the type and location of tickets issued to cyclists in Winnipeg, Manitoba to understand disparities in enforcement. We find that tickets are issued almost exclusively in inner-city areas, with the majority of tickets issued in five census tracts. Tickets were issued in areas that generally had more racialized and immigrant residents, and uniformly had more low-income residents. The unavailability of key data sources limits more in-depth understanding of the impact of policing on equity-seeking groups.